Overall Survival of Breast Cancer Patients With Locoregional Failures Involving Internal Mammary Nodes - Xu, Amy J. (Adv Radiat Oncol, 2019)
PURPOSE: Internal mammary node recurrence after definitive breast cancer treatment is poorly characterized, with limited data to guide clinical management. The aim of this study was to analyze the outcomes of patients with recurrent breast cancer involving internal mammary nodes to understand their natural history and determine prognostic factors associated with improved overall survival. METHODS AND MATERIALS: We performed a retrospective analysis of 553 patients with recurrent breast cancer and identified 161 patients with radiographic evidence of locoregional recurrence as a first event. A total of 67 patients (42%) were identified with internal mammary involvement. Median follow-up times were 76 months from date of initial diagnosis and 30 months from date of recurrence. RESULTS: Of the 67 patients identified with internal mammary node failures, 10 (15%) presented with isolated recurrence, 14 (21%) presented with other sites of locoregional disease, and 43 (64%) presented with concomitant distant metastases. Median overall survival was 2.5 years and significantly associated with extent of disease (P < .0001). On multivariable analysis, concomitant distant metastases, inflammatory breast cancer, and triple negative histologic type were associated with worse overall survival, whereas salvage radiation therapy was associated with improved overall survival. Among the 10 patients with isolated internal mammary node failures, median progression-free survival was 6.0 years and salvage therapy with surgery, radiation, and chemotherapy were associated with the best outcomes. CONCLUSIONS: Patients with isolated internal mammary node recurrences achieved long-term survival with aggressive therapies, and salvage radiation therapy was associated with improved survival.